Central de negócios como instrumento de melhoria de competitividade no setor supermercadista: estudo de caso - Xavier, Aline Pessoa (2009)
The supermarkets of small and medium businesses are facing increased competition in the industry in recent years due to several factors, such as: the strengthening and entry of large national and international networks in Brazil, the proliferation in the number of local competitors and the low power to bargain with suppliers. Given this scenario, small and medium enterprises supermarket of Fortaleza began to look for alternatives to survive. We as an example, the formation of networks of local purchase, whose main goal was to buy products at more competitive prices, besides the exchange of experience. This study finds that the strategies for training of associative networks that help SME’s supermarket become more competitive in an environment of strong competition before the major networks. The methodology of the survey is based on lifting bibliographic, whose goal was to broaden the theoretical knowledge about the formation of strategic business networks. A qualitative research was conducted exploratory in nature with the three networks supermarket from Fortaleza, using a semistructured with the members. What was noted by the field of qualitative research was positive and favorable for the supermarkets that are associated. However, the formation of networks in spite of its importance to keep alive the SME sector’s supermarket can not be adopted as one strategy for its sustainability. We need an administration targeted the needs of customers in each store, as alternatives to maintain their competitiveness.